2021
DOI: 10.3389/fnut.2021.758518
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Overconsumption of Fat and Sugar Causes a Partially Reversible Pre-inflammatory Bowel Disease State

Abstract: Nutrition appears to be an important environmental factor involved in the onset of inflammatory bowel diseases (IBD) through yet poorly understood biological mechanisms. Most studies focused on fat content in high caloric diets, while refined sugars represent up to 40% of caloric intake within industrialized countries and contribute to the growing epidemics of inflammatory diseases. Herein we aim to better understand the impact of a high-fat-high-sucrose diet on intestinal homeostasis in healthy conditions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…21 Subsequent studies indicated that a Western style diet impairs epithelial barrier function in mice and susceptibility to chemically induced (toxic) colitis. [22][23][24] In line with this concept, a glucose-enriched diet deteriorated colitis in IL10 −/− mice and toxic colitis, 25 which was similarly noted for fructose and sucrose enrichment. [26][27][28][29] Not only macronutrients, but also food additives typically enriched in a Western diet (and a related lifestyle) promote susceptibility to colitis.…”
Section: Excessive Intake Of Specific Nutrients or Additives In A Wes...mentioning
confidence: 56%
See 1 more Smart Citation
“…21 Subsequent studies indicated that a Western style diet impairs epithelial barrier function in mice and susceptibility to chemically induced (toxic) colitis. [22][23][24] In line with this concept, a glucose-enriched diet deteriorated colitis in IL10 −/− mice and toxic colitis, 25 which was similarly noted for fructose and sucrose enrichment. [26][27][28][29] Not only macronutrients, but also food additives typically enriched in a Western diet (and a related lifestyle) promote susceptibility to colitis.…”
Section: Excessive Intake Of Specific Nutrients or Additives In A Wes...mentioning
confidence: 56%
“…Saturated and polyunsaturated fatty acids Experimentally promoting gut inflammation, 36 38 arguably restriction in nutritional trials [39][40][41] Restrict animal fat (regardless of source), deep fried and ultra-processed food Sucrose, Glucose, Fructose Experimentally promoting gut inflammation, [23][24][25][26][27] arguably restriction in nutritional trials [39][40][41] Restrict soft drinks, sweets, ready-made food…”
Section: Restrictmentioning
confidence: 99%
“…Animal models utilizing high-fat diets (plus glucose) to induce obesity, metabolic endotoxemia, and insulin resistances show alterations in the gut microbiota [ 28 , 35 ]. In addition, these models have been instrumental in showing that high-fat diets also cause an increase in intestinal permeability and inflammation [ 30 , 59 , 122 , 123 , 124 ]. In human subjects, intestinal inflammation has been observed in more advanced liver diseases such as cirrhosis and HCC [ 125 , 126 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models utilizing high-fat diets (plus glucose) to induce obesity, metabolic endotoxemia, and insulin resistances show alterations in the gut microbiota (18,21). In addition, these models have been instrumental in showing high-fat diets also cause an increase in intestinal permeability and inflammation (45,(112)(113)(114)(115). In human subjects, intestinal inflammation has been observed in more advanced liver diseases like cirrhosis and HCC (116,117).…”
Section: Discussionmentioning
confidence: 99%